Benefits, challenges and opportunities of corporate sustainability - Jacobo-Hernandez, Carlos Armando; Jaimez-Valdez, Miguel Angel; Ochoa-Jimenez, Sergio (Zielona Góra: Faculty of Economics and Management Press)
The topic of corporate sustainability has gained importance in recent years; unfortunately, confusion persists as to what it represents for businesses and academics. This review of the literature aims to analyse concepts and models related to corporate sustainability and to emphasize the most representative recent findings regarding the benefits, challenges, and opportunities of corporate sustainability.
Keywords: management; corporate sustainability; sustainable development; zarządzanie; rozwój firmy; zrównoważony rozwój firmy; rozwój zrównoważony